Investigation of the effect of dopant on catalytic performance of cobalt-oxide powders synthesised by gel casting technique for hydrolysis of NaBH4 - Lee, Jing Hao (Nanyang Technological University, 2015)
The rapid increase in demand for energy in both developed and developing country resulted in the surge in demand for crude oil. Prices of crude oil had seen a 600% increase since the Year 1986. With the world being more aware and concerned about sustainability in energy resources, different energy generation methods have been researched upon. One of such sustainable methods is through the use of hydrogen to generate energy. Several commonly seen methods to generating hydrogen are through techniques such as natural gas reforming, renewable liquid and bio-oil processing, gasification, water electrolytic methods as well as photolytic methods. A particular method which allows portability as well as large scale applications is through the hydrolysis of Sodium Borohydride. Conventional methods of catalysing the reaction is through the use of noble or transition metals, however the use of such metals might incur significant cost. It was found recently that cobalt-based catalyst had comparable catalytic performance and cost only a fraction of that of the use of noble metals. In this project, different kinds of dopants will be doped into cobalt oxide to experiment the effects of the dopants on the catalytic performance. The catalytic performance can be quantified through the use of a hydrogen generation rate measuring device. After which, the phase characteristics of the doped cobalt oxide powders will be determined using X-ray powder diffraction machine. The morphology of the cobalt dopants powders will be determined using the transmission electron spectroscopy and analysed upon to see the characteristics of the particles formed after the doping reaction. Finally the various powders will go through X-ray Photoelectron Spectroscopy to determine the effects of the dopants on binding energy of cobalt oxide. Through the investigation, the characteristics of a high performance doped Cobalt-Oxides powder can be discovered.